2017
DOI: 10.31219/osf.io/h49dg
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Predicting Educational Attainment: Does Grit Compensate for Low Levels of Cognitive Ability?

Abstract: This study examined the role of cognitive ability in moderating grit's predictive effect on educational outcomes. Using a large, representative sample of young adults, we estimated multivariate regression models for the probability of graduating from high school, enrolling in college, earning any college degree, and earning a college degree. For each outcome, the effect of grit (and, alternatively, consistency of interest and perseverance of effort) was allowed to differ for students in each quartile of the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Importantly, some studies have shown that the grit-achievement association could be enhanced in some circumstances, thereby positioning the concept as a potential point of intervention. One study found that the grit effect was more significant at the two ends of the cognitive ability continuum in a nationally representative adult sample (Light and Nencka 2019 ). For adults with low cognitive ability, those with high levels of grit had high education attainments; however, this same effect was not found among adults with average cognitive ability.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, some studies have shown that the grit-achievement association could be enhanced in some circumstances, thereby positioning the concept as a potential point of intervention. One study found that the grit effect was more significant at the two ends of the cognitive ability continuum in a nationally representative adult sample (Light and Nencka 2019 ). For adults with low cognitive ability, those with high levels of grit had high education attainments; however, this same effect was not found among adults with average cognitive ability.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, some studies have shown that the grit-achievement association could be enhanced in some circumstances, thereby positioning the concept as a potential point of intervention. One study found that the grit effect was more significant at the two ends of the cognitive ability continuum in a nationally representative adult sample (Light & Nencka, 2019). For adults with low cognitive ability, those with high levels of grit had high education attainments; however, this same effect was not found among adults with average cognitive ability.…”
Section: Grit and Achievementmentioning
confidence: 99%
“…Beyond being correlated, cognitive and noncognitive skills may also interact by being complements or substitutes in the production function of learning and educational outcomes (Light & Nencka, 2019). We can imagine four ideal types of students with different given combinations of cognitive and noncognitive skills and educational returns, as illustrated in Table 1.…”
Section: Theoretical Background and Previous Findingsmentioning
confidence: 99%
“…Among pupils with low cognitive skills, exerting effort might particularly pay off, substituting their lack of ability to progress in the educational system— skill substitution (e.g., not smart but hardworking ). Whether and how the marginal effects (or the returns) of noncognitive skills on educational outcomes differ across the distribution of cognitive skills is an open empirical question (Light & Nencka, 2019).…”
Section: Theoretical Background and Previous Findingsmentioning
confidence: 99%
See 1 more Smart Citation